Pola Pelatihan UKM Dharmagita Jawa Dalam Penguatan Pendidikan Karakter Mahasiswa di Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar - Adi Prasetya, I Putu (Jayapangus Press, 2021)
Universities facing the era of globalization and competitive competition, especially in the field of education, require capabilities in the form of hard skills and soft skills. Soft skills in the world of education, especially higher education, can be obtained from participation in activities that train non-academic capabilities such as Student Activity Units or what is interpreted as UKM. The I Gusti Bagus Sugriwa State Hindu University campus in Denpasar has 26 Student Activity Units (UKM), one of which is the Dharmagita Jawa UKM. In the Javanese Dharmagita Training, the supervisors or administrators of the student activity units have a pattern or method for developing the Javanese Dharmagita through a series of activities that not only focus on Dharmagita training but also carry out activities that foster the strengthening of behavioral education in students. Based on Lickona's opinion, it is explained that behavior consists of three correlated components, namely moral knowing, moral feeling, and moral behavior. The Moral Knowing that students get during the Training stage and the activities carried out include: 1). Member training, 2) Javanese ballad training, 3). Javanese dance training, 4). Provision of Dharmawacama and Dharmatula, 5). Ambal Warsa, 6). Devotion, 7). Annual deliberation, along with 8). Evaluation/assessment. There are obstacles and efforts made during the training, whether from trainers or students. The implications obtained from the Dharmagita Java UKM training are the implications for moral feelings along with the implications for moral behavior. Moral Feeling is an emotional aspect that can be felt and applied directly by students through behavioral norms, namely: Religious, nationalist, independent, mutual cooperation, integrity. In moral behavior in this research, students can implement behavioral norms in their daily routines in the form of behavior, movements or actions. Therefore, the Dharmagita Java UKM training pattern in the strengthening stage of behavioral education is crucial to be implemented so that students have soft skills that will be useful later both for the students themselves and also the community when they finish college.